Penyuluhan Pernikahan Dini Dalam Perspektif Hukum Islam Di Kabupaten Blora: Membangun Kesadaran Hukum Dan Sosial Masyarakat - Ade Falah (https://journal.metanusantara.com/impact/index.php/jpk, 2025)
This study aims to analyse the understanding and attitudes of the people of Blora Regency towards early marriage in the perspective of Islamic law and to assess the effectiveness of the extension programme that has been implemented. This type of research is qualitative with a descriptive approach. Data sources were obtained through interviews with 100 informants, consisting of community members, religious leaders, and legal counsellors in Blora District. The purpose of this study was to understand the level of community understanding of early marriage according to Islamic law and evaluate the effectiveness of counselling in changing community attitudes towards the issue. The results show that most people in Blora district (60%) understand early marriage as discouraged in Islam, but only 40% have an in-depth understanding of its long-term impacts. Counselling by the government and local community organisations has been successful in improving basic understanding, but its effectiveness in changing people's attitudes is limited, with only 30% of respondents finding counselling effective. Cultural factors and social norms that still favour early marriage are the main barriers to attitude change. The study concludes that more effective social change requires a more inclusive and adaptive approach to local needs, as well as the use of more accessible media, such as information technology and social media.